2015
DOI: 10.1007/978-3-319-24553-9_74
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning and Structured Prediction for the Segmentation of Mass in Mammograms

Abstract: In this paper, we explore the use of deep convolution and deep belief networks as potential functions in structured prediction models for the segmentation of breast masses from mammograms. In particular, the structured prediction models are estimated with loss minimization parameter learning algorithms, representing: a) conditional random field (CRF), and b) structured support vector machine (SSVM). For the CRF model, we use the inference algorithm based on tree re-weighted belief propagation with truncated fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
104
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(105 citation statements)
references
References 17 publications
1
104
0
Order By: Relevance
“…Although these methods achieved promising results in cases of adenoma and well differentiated (low grade) adenocarcinoma, they may fail to achieve satisfying performance in malignant subjects, where the glandular structures are seriously deformed. Recently, deep neural networks are driving advances in image recognition related tasks in computer vision [21,9,7,27,29,3] and medical image computing [10,30,31,6,12]. The most relevant study to our work is the U-net that designed a U-shaped deep convolutional network for biomedical image segmentation and won several grand challenges recently [30].…”
Section: Introductionmentioning
confidence: 99%
“…Although these methods achieved promising results in cases of adenoma and well differentiated (low grade) adenocarcinoma, they may fail to achieve satisfying performance in malignant subjects, where the glandular structures are seriously deformed. Recently, deep neural networks are driving advances in image recognition related tasks in computer vision [21,9,7,27,29,3] and medical image computing [10,30,31,6,12]. The most relevant study to our work is the U-net that designed a U-shaped deep convolutional network for biomedical image segmentation and won several grand challenges recently [30].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, unlabeled imaging data and unsupervised feature learning (e.g., sparse autoencoder) have been explored for breast density segmentation and risk scoring . Deep convolution and deep belief networks have been integrated in structured prediction models for mammographic breast mass segmentation …”
Section: Introductionmentioning
confidence: 99%
“…18 Deep learning coupled with big training data has shown promising capability in many artificial intelligence applications 19,20 and, more recently, biomedical imaging analysis. For example, deep learning has been used for thoraco-abdominal lymph node detection and interstitial lung disease classification, 21 realtime 2D/3D registration of digitally reconstructed X-ray images, 22 breast lesion detection and diagnosis, [23][24][25][26][27] radiological imaging segmentation, 28,29 as well as digital breast pathology image analysis 27,30 such as mitosis detection and counting, tissue classification (e.g., cancerous vs. non-cancerous), segmentation (e.g., nuclei or epithelium), 30 and metastatic cancer detection from whole slide images of sentinel lymph nodes. 27 Many such studies have shown that automatic feature extraction using deep learning outperformed traditional hand-crafted imaging descriptors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second is the poor contrast of the mammographic images which makes the model predict blurry boundaries and yields inaccurate predictions inside the boundaries. Some works use the structural learning to cope with this difficulty [7,28]. However, the two-stage training used in these works cannot fully explore the power of potential functions.…”
Section: Introductionmentioning
confidence: 99%